Adeno-Associated Virus (AAV) as a Vector for Gene Therapy - Naso, Michael F. (BioDrugs, 2017)
There has been a resurgence in gene therapy efforts that is partly fueled by the identification and understanding of new gene delivery vectors. Adeno-associated virus (AAV) is a non-enveloped virus that can be engineered to deliver DNA to target cells, and has attracted a significant amount of attention in the field, especially in clinical-stage experimental therapeutic strategies. The ability to generate recombinant AAV particles lacking any viral genes and containing DNA sequences of interest for various therapeutic applications has thus far proven to be one of the safest strategies for gene therapies. This review will provide an overview of some important factors to consider in the use of AAV as a vector for gene therapy.